Problematic Issues of E-Banking Management in Bangladesh - Redwanuzzaman, Md.; Islam, Md. Amirul (Asian Business Review, 2013)
In Bangladesh, banking industry is getting mature to a great extent than earlier period. With the launching of internet the world has become a smaller one. Remarkable development in ICT has introduced a global revolution in banking sectors. Beside the every sector in social life it has rendered enormous impacts on banking sector. Internet together with other information and communication technologies are not only driving financial global economies but also transforming societies into knowledge-based economies around the world. As a third world developing country, Bangladesh is far behind to reach the expected level in global banking system. So it is our urgent need to upgrade its banking system. The main focus of this study is to examine the performance, problems and prospects of E-banking in Bangladesh. This paper is also aimed at to determine the present scenario of e-banking and banking sectors in Bangladesh and at the same time it demonstrated the scope and benefits of e-banking compared with the existing sector. The study is descriptive in nature. So this study has been done mainly based on secondary sources of data or information which sources included different published articles, books, newspaper, and websites.JEL Classification Code:  G29
Keywords: Electronic Banking; Bank; Bangladesh